Childhood determinants of suicidality in men recently transitioned from regular military service. (July 2020) - Syed Sheriff, Rebecca; Van Hooff, Miranda; Malhi, Gin S; Grace, Blair; McFarlane, Alexander
Objective: Rates of suicidality are higher in military than comparable civilian populations. The period of transition from regular military service may be a time of particular vulnerability. In order to best inform early intervention and prevention strategies, we sought to investigate the childhood determinants (trauma and disorder) of self-reported past-year suicidality (thoughts, plans or attempts) in a population of Australian Defence Force men who had recently (in the previous 5 years) transitioned from regular military service. Methods: We analysed self-report, and detailed interview, cross-sectional data to investigate the association between retrospectively reported past-year suicidality and childhood factors (disorder and trauma) and whether these relationships were independent of each other and adult-onset trauma and disorder. We utilised logistic regression techniques and generalised structural equation modelling. Results: The prevalence of suicidality in transitioned men was 21.6% (95% confidence interval [CI]: [19.9, 23.3]). Suicidality was associated with childhood-onset interpersonal trauma and anxiety and adult-onset anxiety and depression. Generalised structural equation modelling demonstrated that the pathway between childhood interpersonal trauma and suicidality was not fully mediated by childhood anxiety. Restricting the analyses to those previously deployed demonstrated that suicidality had a direct and significant association with childhood-onset factors (anxiety and interpersonal trauma) and adult-onset trauma (deployment and non-deployment related). Conclusion: This study sheds light onto the significance of childhood factors (interpersonal trauma and anxiety) in a population undergoing transition that may revive pre-existing vulnerabilities. These findings have the potential to aid early intervention and prevention strategies in identifying those at risk prior to transition. These findings also imply that early interventions targeting anxiety and interventions to reduce social instability during the transition period may be useful in reducing suicidality during this time. Further prospective studies are needed to further explore these novel findings.